Evolution of biofuels: Unraveling diverse applications and emerging horizons - Fatima Akram; Esha Shoaib; Taseer Fatima; Ifrah Shabbir; Ikram-ul Haq (Energy Exploration & Exploitation)
The comprehensive review presents multi-faceted biofuel applications in various sectors and prospects, highlighting state-of-the-art technologies and potential changes in triglyceride-based biofuels. From the first-generation biofuel produced from food crops to the fourth generation of engineered microbes, there is an improvement in technologies and sustainability. Transesterification synthesis of biodiesel with different chemical catalysts and biocatalysts shows continuous efforts toward making the process more efficient and economically viable; emerging technologies like hydrodeoxygenation and pyrolysis open new routes for optimized biofuel production with less environmental impact. With a focus on biodiesel, bioethanol, biobutanol, and biohydrogen, this paper deals with their contributions to energy generation in a sustainable manner and environmental stewardship. AI and machine learning in the production of biofuels could provide new revolutions in efficiency and sustainability directly from feedstock selection to product recovery. Bioethanol is effectively used in gasoline blends with several advantages, reducing carbon dioxide emissions. Biobutanol is a good transport fuel alternative, with high energy content, easily used with the existing infrastructure. Biological processes yield Biohydrogen and may have bright prospects for producing clean energy, specifically in the case of bioelectrochemical systems. Prospects hinge on addressing the challenges, promoting research and development, and fostering collaboration and investment in biofuel innovation. This review underscores the importance of continued efforts to advance biofuel technologies, recognizing their pivotal role in achieving a sustainable energy future while addressing global energy and environmental challenges.